PENGARUH MUTASI KERJA DAN PROMOSI JABATAN TERHADAP MOTIVASI KERJA APARATUR SIPIL NEGARA (ASN) PADA SEKRETARIAT DAERAH KABUPATEN KERINCI: ADE NURMA JAYA PUTRA, S.Sos., M.A.P - ade nurma jaya (JURNAL ADMINISTRASI NUSANTARA, 2020)
This study aims to determine the effect of mutation and promotion of position on work motivation. The number of samples determined was 68 respondents using the Quantitative method. As an independent variable, namely work mutation and promotion while the dependent variable is work motivation. The analysis used is multiple linear analysis includes, coefficient of determination and hypothesis testing. The results of the analysis using multiple linear can be seen that the mutation variable affects motivation by 1,227 (122%) and Job Promotion affects Work Motivation by 0.067 (6.7%) both of these variables affect the performance and the results of the analysis using the coefficient of determination is known that 0.962 (96.2%) Variations in work motivation can be explained by the independent variables examined in this study and 3.8% are explained by other factors beyond this discussion. And the results of hypothesis testing both partially and simultaneously that the independent variable on the dependent variable there is a significant influence using the t-test and f-test